Did the 1999 NYSE and NASDAQ Listing Standard Changes on Audit Committee Composition Benefit Investors? - Kim, Seil; Klein, April (The Accounting Review, 2017)
ABSTRACT In December 1999, the SEC instituted a new listing standard for NYSE and NASDAQ firms. Listed firms were now required to maintain fully independent audit committees with at least three members. In July 2002, the U.S. Congress legislated these standards through the Sarbanes-Oxley Act. Our research question is whether all investors benefited from the 1999 new rule. Using both an event study and a difference-in-differences methodology, we find no evidence of higher market value or better financial reporting quality resulting from this rule.